AB0473 Effects of CTLA4-IG (Abatacept) on Endothelial Cell Cultures After Different Times from Treatment. (9th June 2015) - Cutolo, M.; Soldano, S.; Contini, P.; Trombetta, A.C.; Sulli, A.; Seriolo, B.; Cimmino, M.A.; Paolino, S.; Pizzorni, C.; Montagna, P.; Brizzolara, R.
Abstract : Background: Endothelial cell (EC) dysfunction is involved in the angiogenetic processes observed in rheumatoid arthritis (RA) synovitis [1]. CTLA4-Ig (abatacept) is employed as biological agent in RA treatment and interacts in vitro with the costimulatory molecule CD86 (B7.2) expressed by different cells involved in the process, including ECs [2-4]. Objectives: To evaluate the expression of CD86, CD54 (ICAM1, intercellular adhesion molecule 1) and CD309 (VEGFR-2, vascular endothelial growth factor receptor 2) on cultured human microvascular endothelial cells (HMVECs), activated with γIFN, treated with abatacept (ABAT) and tested after different times from treatment. Methods: HMVECs (Lonza, Switzerland) were activated with γIFN (500 U/ml), treated with ABAT (10, 50, 100, 500 μg/ml) and evaluated after different times of incubation (24, 48, 72 hrs and 7 days). Evaluation of CD86, CD54, CD309 expression were performed at fluorescence-activated cell sorting analysis (FACS, FC500, Coulter, Hialeah, FL) immediately after the first activation with γIFN (control) and after each ABAT treatment (24, 48, 72 hrs and 7 days). Results: FACS analysis showed in activated HMVECs a decrease of the CD86+ cell percentage, after 24 and 48 hrs from ABAT (500 μg/ml) treatment (77% and 69% CD86+ cells, respectively) and after 48 hrs from ABAT (100 μg/ml) treatment (93% CD86+ cells), compared to the untreated controls (97% CD86+ cells). On the contrary, no reductions regarding the % of CD86+ cells were further detectable after 72 hrs and 7 days, compared to basal values. No changes were observed after other ABAT doses (10 and 50 μg/ml). There was a reduction in the percentage of CD54+ cells at all time points after treatment with ABAT (48 hrs, 72 hrs and 7 days). Interestingly, after only 24 hours ABAT (100 and 500 μg/ml) induced a decrease of the absolute percentage of CD54+ cells (18% and 20% CD54+, respectively) compared to controls (42% CD54+ cells). On the other hands, CD309+ cells showed a % decrease (71% and 41%, respectively) after 24 hrs from ABAT treatments (both 100 and 500 μg/ml) and after 48 hrs from ABAT (500 μg/ml) treatment (62% CD309+ cells), compared to the control (96% CD309+ cells). No changes for the % of CD309+ cells were observed after other ABAT concentrations (10 μg/ml and 50 μg/ml). Conclusions: These preliminary results show that a stable ABAT/CD86 interaction may be obtained in cultured ECs, after 24 or 48 hrs from ABAT treatment (100 and 500 μg/ml), resulting in a decreased percentage of CD54+ and CD309+ cells. Although these concentrations are higher than the trough concentrations of abatacept in vivo, they may be physiologically relevant at sites of inflammation such like in RA synovitis. References: Marrelli A et al. Autoimmun Rev. 2011;10:595-8. Cutolo M et al. Autoimmun Rev. 2013;12:758-67. Cutolo M et al. Clin Exp Rheumatol. 2013;31:943-6. Kreisel D et al. J Immunol 2002;169:6154-61. Acknowledgements: The study was partially supported by research grant (university funds) by Bristol Myers Squibb and the compound for the experiments was provided by Bristol Myers Squibb. Disclosure of Interest: M. Cutolo Grant/research support from: The study was partially supported by research grant (university funds) by Bristol Myers Squibb and the compound for the experiments was provided by Bristol Myers Squibb., S. Soldano: None declared, P. Contini: None declared, A. C. Trombetta: None declared, A. Sulli: None declared, B. Seriolo: None declared, M. A. Cimmino: None declared, S. Paolino: None declared, C. Pizzorni: None declared, P. Montagna: None declared, R. Brizzolara: None declared